Spontaneous rectus sheath haematoma in a deceased donor renal transplant recipient: a rare complication - Sreenivas, Jayaram (BMJ Case Rep, 2016)
Rectus sheath haematoma (RSH) is rarely thought of as a cause of abdominal pain in renal transplant recipients. A 36-year-old woman, a post-deceased donor renal allograft transplant recipient for chronic interstitial nephritis, on triple drug immunosuppression (tacrolimus, mycophenolate mofetil and prednisolone) with basiliximab induction, developed acute vascular rejection and acute tubular injury with suspected antibody-mediated rejection. While on plasmapheresis and haemodialysis for delayed graft function, she developed acute left lower abdominal pain on the 16th postoperative day with tender swelling in the left paraumbilical region. CT of the abdomen showed a large haematoma in the left rectus sheath with no extension. The patient underwent haematoma evacuation through a left paramedian incision and had an uneventful recovery. Serum creatinine stabilised at 0.8 mg/dL and she is on regular follow-up with excellent graft function at 6 months. Diagnosis requires a high index of suspicion, and prompt treatment prevents morbidity and can expedite patient recovery.